Synthesis and characterization of organotin (IV) complexes with hydrazone/carbohydrazone ligand - Panggai, Margaret (Universiti Malaysia Sarawak (UNIMAS), 2008)
Six organotin(IV) complexes of carbohydrazone-bis(benzaldehyde) ligand (1) with RnSnCl4-n (R= Me, Bu and Ph, n = 1, 2) have been synthesized in refluxing methanol under N2 atmosphere. Another, two organotin(IV) complexes of benzophenone-salicylhydrazone ligand (2) have also been synthesized with the same method but in the presence of base in refluxing methanol in 1:1 mole ratio. All organotin(IV) complexes (3-10) have been characterized by different physicochemical techniques like CHN analyses, UV-visible and IR spectral studies. Among them, ligand (2) and its diphenyltin(IV) complex (9) have also been characterized by 1H NMR spectral analyses. All organotin(IV) complexes are non electrolytic in nature. Spectral studies suggest that ligand (1) act as bidentate nature while the ligand (2) act as a mononegative bidentate nature in their organotin(IV) complexes. Five- and six- coordinated molecular structures have been proposed for all the organotin(IV) complexes.